Фізичні основи оптичного запису та обробки інформації - Кононенко, К. О. (ХНУРЕ, 2023)
This work is devoted to the physical foundations of optical recording and information processing. The principle of operation of the method of optical recording of information and its processing are considered. It is told about the history of optical recording of information and its stages. The structural laughter of optical methods of information processing is given. The main advantages of optical information processing systems are mentioned. The areas of practical use of optical information processing systems are established